La religión como fenómeno antropológico – Elementos constitutivos del fenómeno religioso - Gómez, Salustiano Alvarez (Horizonte, 2004)
The religious phenomenon is present in cultures as a response to fundamental human questions. It shapes the understanding of life and elaborates cosmologies. With basis on its intuition, it organises itself elaborating the feelings of the sacred, symbolic realities, rites, ethics, and so on, which establish forms of social and communitarian relations.